2021
DOI: 10.2991/chi.k.210718.001
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Troponin T and NT-proBNP in Patients Receiving Chimeric Antigen Receptor (CAR) T-Cell Therapy

Abstract: Retrospective studies suggest that chimeric antigen receptor T-cell (CAR T) therapy may lead to cardiac injury, but this has not been assessed systematically or prospectively. In this prospective study of 40 patients who received CAR T, we systematically measured high-sensitivity troponin T (hsTropT) and N-terminal pro-B natriuretic peptide (NTproBNP) at baseline and on day 1, days 7, and 21 after CAR T. Biomarker elevations with respect to timepoint and cytokine release syndrome (CRS) status were examined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…While it is not fully understood, the discrepancy of cardiac biomarkers could be explained by physiologic changes (unfavorable hemodynamic profile with altered diastolic function) associated with atrial fibrillation before myocardial injury [ 23 ]. A recent report showed similar results where the authors prospectively analyzed high-sensitivity troponin-T and NT-pro BNP levels at baseline, and days 1, 7 and 21 after CAR-T [ 24 ]. It was also found that troponin-T did not change during CAR-T therapy, but NT-proBNP levels were elevated on day 7.…”
Section: Discussionmentioning
confidence: 58%
“…While it is not fully understood, the discrepancy of cardiac biomarkers could be explained by physiologic changes (unfavorable hemodynamic profile with altered diastolic function) associated with atrial fibrillation before myocardial injury [ 23 ]. A recent report showed similar results where the authors prospectively analyzed high-sensitivity troponin-T and NT-pro BNP levels at baseline, and days 1, 7 and 21 after CAR-T [ 24 ]. It was also found that troponin-T did not change during CAR-T therapy, but NT-proBNP levels were elevated on day 7.…”
Section: Discussionmentioning
confidence: 58%
“… 66 Indeed, in another study by Hu et al . 47 there was no associations observed between cTN levels and CAR-T-associated toxicity. The potential clinical utility of serum cTN as a biomarker to monitor toxicity associated with the TKIs have been investigated.…”
Section: Circulating Biomarkers For Ctrcdmentioning
confidence: 71%
“… 46 In another small prospective study NT-proBNP, as opposed to cTn levels, were increased in the days after chimeric antigen receptor (CAR) T-cell (CAR-T) therapy and significant differences in NT-proBNP levels were observed between patients with and without CAR-T-associated cytokine release syndrome. 47 …”
Section: Circulating Biomarkers For Ctrcdmentioning
confidence: 99%
“…Limited conclusions can be drawn from this study because of the small sample size and potential selection bias, as per institutional protocol, they could not enroll subjects who experienced acute coronary syndrome (unstable angina, non-ST segment elevation myocardial infarction, or ST segment elevation myocardial infarction) in the previous year to get CAR-T therapy. 41 All patients who experience cardiotoxicity warrant follow-up with a cardio-oncologist, with timing dictated by the severity of CV toxicity (Fig 1 ), to ensure adequate GDMT, and conduct routine laboratory work and noninvasive cardiac imaging to assess for improvement in cardiac function. It is important to note that prospective longitudinal studies are warranted to understand the long-term implications of CAR-T on CV health, particularly the risk of developing hypertension, HF, CAD, and metabolic syndrome after a latent period after CAR-T because of immune system alterations.…”
Section: Post-treatment Surveillance and Follow-upmentioning
confidence: 99%